2010
DOI: 10.1111/j.1540-8159.2009.02613.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Superior Vena Cava Syndrome as a Complication of Pacemaker Implantation: A Pooled Analysis of Clinical Practice

Abstract: Currently, transvenous stenting is the most common treatment used for pacemaker-related SVCS, usually with conservation of the implanted leads. Both surgery and stenting appear to be effective treatments, with low incidences of recurrent SVCS over the first 12 months, but there is unfortunately a paucity of data on long-term outcomes. (PACE 2010; 420-425).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 66 publications
1
71
0
Order By: Relevance
“…Although infrequent, multiple reports of superior vena cava (SVC) syndrome exist in the literature. [75][76][77][78][79][80][81][82] Risk factors for the development of SVC syndrome include device infection, polyurethane leads, thrombophilia, and multiple leads. 80 -82 As a result, the 2009 Heart Rhythm Society Expert Consensus on Lead Extraction 23 has assigned a class IIa indication to lead extraction for a CIED procedure that would result in Ͼ4 leads on 1 side or 5 leads through the SVC.…”
Section: Lead Burden and The Central Venous Systemmentioning
confidence: 99%
“…Although infrequent, multiple reports of superior vena cava (SVC) syndrome exist in the literature. [75][76][77][78][79][80][81][82] Risk factors for the development of SVC syndrome include device infection, polyurethane leads, thrombophilia, and multiple leads. 80 -82 As a result, the 2009 Heart Rhythm Society Expert Consensus on Lead Extraction 23 has assigned a class IIa indication to lead extraction for a CIED procedure that would result in Ͼ4 leads on 1 side or 5 leads through the SVC.…”
Section: Lead Burden and The Central Venous Systemmentioning
confidence: 99%
“…There is no current consensus about their relative efficacy and merits. Riley et al (2010) recently reviewed and summarized all of the reported cases of this complication that were treated in order to aid clinical decision making and spur future research in this area. It was recognized from the outset of this venture that any attempt at a pooled analysis of results could be significantly hampered by the small number of cases in each treatment group and publication bias, particularly the underreporting of treatment failures and of SVCS recurrences after initially successful interventions.…”
Section: Superior Vena Cava Syndromementioning
confidence: 99%
“…Surgical approaches for bypass or reconstruction exist but are rarely used in the modern era. 23 An alternative option, percutaneous venoplasty, is being increasingly utilized as a safe and effective method to preserve ipsilateral access even in the setting of chronic occlusion. Worley and colleagues 24 reported successful venoplasty in 371 of 373 consecutive patients (over an 11-year period) who were found to have significant subclavian stenosis while undergoing lead revision or upgrade.…”
Section: Managementmentioning
confidence: 99%
“…Anticoagulation and thrombolytic therapy also have been utilized, but they are unlikely to be effective for the chronic fibrotic lesions that often exist in these patients. 23 For the persistent symptomatic patient, device extraction can be considered, but this comes with an approximately 1-2% risk of significant morbidity and mortality, including tamponade, valve injury and hemothorax. 11 Venoplasty with or without stenting is an alternative approach that enables the device and leads to stay in place, avoiding the risks of lead extraction as well as preserving ipsilateral access.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation